2018
DOI: 10.1002/ppul.23946
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal swallowing assessment using fiberoptic endoscopic evaluation of swallowing (FEES)

Abstract: Aspiration is very frequent in premature infants who present desaturations during feeding and FEES is a useful method for diagnosing and suggesting treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…Literature shows that penetration is linked to tracheal aspiration ( 22 ). Our pilot data showed that FEES detected more penetration than VFSS, which corroborates with available evidence reported in both the pediatric ( 4 , 23 25 ) and adult literature ( 20 , 26 , 27 ). This supports the notion that FEES is more sensitive than VFSS in detecting penetration.…”
Section: Discussionsupporting
confidence: 91%
“…Literature shows that penetration is linked to tracheal aspiration ( 22 ). Our pilot data showed that FEES detected more penetration than VFSS, which corroborates with available evidence reported in both the pediatric ( 4 , 23 25 ) and adult literature ( 20 , 26 , 27 ). This supports the notion that FEES is more sensitive than VFSS in detecting penetration.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to patients without known dysphagia, the goal for patients with previously diagnosed pharyngeal dysphagia may be to trial a specific consistency with the hope of either adjusting the diet, or reassessing safety in the setting of fluctuating clinical symptoms . Under these circumstances, an abnormal SEES may allow one to avoid a repeat VFSS even if FEES is unsuccessful, as a known abnormality on VFSS will be predictably present in nearly 90% of patients based on our results.…”
Section: Discussionmentioning
confidence: 88%
“…These findings have several implications worthy of discussion. In a child who is otherwise naive to instrumental swallow studies and without an established diagnosis of swallow dysfunction, one may wonder if a VFSS is necessary to perform following an abnormal FEES, as it may not provide additional insight . However, if a SEES is performed and is abnormal, VFSS may be more assertively avoided, as swallow abnormalities are likely to exist based on the positive predictive value of the static evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of oral aspiration and penetration are elevated in premature infants, and an abnormal VFSS tended to be commoner among premature infants in our study, although the difference was not statistically significant. 23 The relatively high rates of prematurity in our population may have increased the prevalence of abnormal VFSS, but would not be expected to affect rates of the laryngeal cleft. In Duncan et al 13 series of 137 infants with isolated laryngeal penetration, 35% were premature.…”
Section: Genetic Causes Of Laryngeal Cleft Include 22q Deletion Syndrmentioning
confidence: 81%